Influence of phonon confinement on the optically detected electron-phonon resonance linewidth in quantum wells. (June 2016) - Hien, Nguyen Dinh; Dinh, Le; Lam, Vo Thanh; Phong, Tran Cong
Abstract: We investigate the influence of phonon confinement on the optically detected electrophonon resonance (ODEPR) effect and ODEPR line-width in quantum wells. The obtained numerical result for the GaAs/AlAs quantum well shows that the ODEPR line-widths depend on the well's width and temperature. Besides, in the two cases of confined and bulk phonons, the linewidth (LW) decreases with the increase of well's width and increases with the increase of temperature. Furthermore, in the small range of the well's width, the influence of phonon confinement plays an important role and cannot be neglected in considering the ODEPR line-width.